2008
DOI: 10.1017/s0014479708006170
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFYING SEED UPTAKE PATHWAYS: THE SPREAD OFAGYA AMOAHRICE CULTIVAR IN SOUTHWESTERN GHANA

Abstract: A study was carried out to identify the factors that contributed to the natural spread and uptake of a rainfed rice variety named Agya Amoah in the Western Region of Ghana after introduction of a small amount (0.5 kg) of seed in 1987 by a small-scale farmer. Fifteen years after its introduction over 73% of rice farmers had grown the variety in the Western Region. Initial awareness of the variety was created by information provided mainly by friends, seeing the variety grown in fields and from relatives. Seed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…Own stocks were also important, providing 1/3 of seed sown overall, varying between 28 and 45 % in all sites, with the exception of Haiti. The secondary rather than primary importance of use of own stocks challenges several common stereotypes: first, the notion that smallholder farmers will prioritize seed saving in times of stress (De Waal 1991) and, second, that own-saved seed provides the bulk of smallholder sowings (e.g., Bezner Kerr 2013; Cavatassi et al 2011;Guei et al 2011;Marfo et al 2008). Simply, overall data show that the locus of seed sources is off-farm, not within farm.…”
Section: Across Cropsmentioning
confidence: 99%
“…Own stocks were also important, providing 1/3 of seed sown overall, varying between 28 and 45 % in all sites, with the exception of Haiti. The secondary rather than primary importance of use of own stocks challenges several common stereotypes: first, the notion that smallholder farmers will prioritize seed saving in times of stress (De Waal 1991) and, second, that own-saved seed provides the bulk of smallholder sowings (e.g., Bezner Kerr 2013; Cavatassi et al 2011;Guei et al 2011;Marfo et al 2008). Simply, overall data show that the locus of seed sources is off-farm, not within farm.…”
Section: Across Cropsmentioning
confidence: 99%
“…For example, 3 years after the distribution of high-yielding Carioca bean seeds to 400 farmers in Zambia in 1986, 3.7 times as many farmers were estimated to be growing the new variety, although only about half of the farmers who originally received the seed were still sowing it (Grisley and Shamambo 1993). Fifteen years after the introduction of 0.5 kg of seed of a new rice variety to a single farmer in Ghana in 1987, about 73 % of farmers in the Western part of Ghana were believed to have grown the new variety (Marfo et al 2008). Such introductions of new varieties have occurred innumerable times over the last decades, but there has been little recording of if, how, and why they spread among farmers under various conditions (Witcombe et al 1999).…”
Section: Seed Release and Public Good Experimentsmentioning
confidence: 99%
“…Tripp and Rohrbach (2001) found that most smallholder farmers either give or receive seed each year, through gifts or barter and also sales. However, networks link relatives and friends more closely than neighbours (Marfo et al, 2008). Seed networks may be limited by class barriers, while migration and increased market production tend to fragment seed exchange networks (Almekinders et al, 2007).…”
Section: The Supply Of Common Seedmentioning
confidence: 99%